STUDI RASIONALITAS PENGGUNAAN OBAT ANTIDIABETES PADA PASIEN DIABETES MELITUS TIPE 2 DI RSU IMELDA PEKERJA INDONESIA - Mutiara Siahaan; Sukri Ramadhan (SUAN PUBLISHER, 2025)
Diabetes Mellitus (T2DM Type 2 is a chronic metabolic disorder characterized by hyperglycemia due to insulin resistance and impaired insulin secretion. The management of T2DM requires rational pharmacological therapy to achieve optimal glycemic control and prevent complications. This study aimed to evaluate the rationality of antidiabetic drug use in T2DM patients at RSU Imelda Pekerja Indonesia, including aspects of appropriate indication, appropriate drug, appropriate dose, appropriate patient, and appropriate route of administration, as well as to identify the patterns of antidiabetic drug use. This research employed a descriptive observational design with a retrospective approach. Data were collected from the medical records of T2DM outpatients during the period of May–July 2025 with a total sample of 46 patients, selected using purposive sampling. Data were analyzed descriptively by referring to the Indonesian PERKENI 2024 guideline. The pattern of antidiabetic drug use showed that metformin was the most frequently prescribed agent, either as monotherapy or in combination with sulfonylureas (glimepiride/gliclazide MR). The evaluation of rationality demonstrated: appropriate indication (100%), appropriate drug (93.5%), appropriate dose (91.3%), appropriate patient (95.6%), and appropriate route of administration (100%). Overall, the use of antidiabetic drugs at RSU Imelda Pekerja Indonesia was rational. The use of antidiabetic drugs in T2DM patients at RSU Imelda Pekerja Indonesia has been rational according to the five parameters of rationality. These findings support the study hypothesis that antidiabetic drug use is in accordance with therapeutic standards.